PENGEMBANGAN BAHAN AJAR KALKULUS INTEGRAL DENGAN PENDEKATAN APTITUDE TREATMENT INTERACTION (ATI) BERBANTU MACROMEDIA FLASH - Venty Meilasari (Eksponen, 2020)
ABSTRACT The difficulty of students in understanding the material in the integral calculus print book is one factor that makes student learning outcomes low. The difference in students' abilities is one of the considerations in developing process. This study aims to develop integral calculus teaching material using the aptitude treatment interaction (ATI) approach assisted by Macromedia flash. This research belongs to the development research. The instruments used in this study were questionnaires and tests. Indicators of the results of this study are teaching materials declared worthy of use and students who get optimal learning outcomes> 75%. The stages in the study consisted of ten stages that began with discovering potentials and problems to mass production. The results of the study showed that the integral calculus teaching material made was feasible to use. As many as 79% of students achieve optimal learning outcomes.